Evaluasi implementasi program anti pencucian uang di Indonesia - Fany Dewi Rengganis; Dwi Setiawan Susanto (Integritas: Jurnal Antikorupsi, 2023)
The term money laundering emerged in the early 19th century. Although various prevention and enforcement efforts have been developed since then, money laundering still occurs throughout the world. Therefore, it is necessary to carry out continuous evaluations to ensure that the applicable policies to curb money laundering remain adequate. This research aims to evaluate the effectiveness of anti-money launder-ing programs in Indonesia using the opportunity element approach in fraud models that are represented by the regulations, implementations, and supervisions. This research will evaluate: (1) the effectiveness of money laundering control, (2) banks levels of compliance, (3) the regulatory and supervisory body’s performance, and (4) the problems in implementation of the anti-money laundering program. This study uses a qualitative research method with an evaluation approach. This study obtained data from Indonesia’s Financial Service Authority, the Financial Intelligence Unit and the relevant banks as well as other relevant evaluations reports and indexes. The results of this study are that the implementation of the AML program in Indonesia is good but still needs improvement in its risk-based preventive measure and enforcement measures. The results of this research also shows that the identification of beneficial owner is one of the problems faced by banks.